2019
DOI: 10.3390/cancers11121931
|View full text |Cite
|
Sign up to set email alerts
|

The Adipose Stem Cell as a Novel Metabolic Actor in Adrenocortical Carcinoma Progression: Evidence from an In Vitro Tumor Microenvironment Crosstalk Model

Abstract: Metabolic interplay between the tumor microenvironment and cancer cells is a potential target for novel anti-cancer approaches. Among stromal components, adipocytes and adipose precursors have been shown to actively participate in tumor progression in several solid malignancies. In adrenocortical carcinoma (ACC), a rare endocrine neoplasia with a poor prognosis, cancer cells often infiltrate the fat mass surrounding the adrenal organ, enabling possible crosstalk with the adipose cells. Here, by using an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…The effect has been mainly described in stromal fibroblast cells, however given that ASCs and CAA are fibroblast like cells, it is likely they are also important contributors. Indeed it has been reported that the “reverse Warburg effect” was induced during the co-culture of adrenocortical carcinoma cells with ASCs [ 132 ]. Ketone bodies are another catabolite produced and released by glycolytic adipocytes and they are an ideal substrate for ATP production by driving oxidative mitochondrial metabolism leading to enhanced tumor invasiveness [ 91 , 133 ].…”
Section: Mechanisms Linking Adipose Tissue To the Metastatic Cascamentioning
confidence: 99%
“…The effect has been mainly described in stromal fibroblast cells, however given that ASCs and CAA are fibroblast like cells, it is likely they are also important contributors. Indeed it has been reported that the “reverse Warburg effect” was induced during the co-culture of adrenocortical carcinoma cells with ASCs [ 132 ]. Ketone bodies are another catabolite produced and released by glycolytic adipocytes and they are an ideal substrate for ATP production by driving oxidative mitochondrial metabolism leading to enhanced tumor invasiveness [ 91 , 133 ].…”
Section: Mechanisms Linking Adipose Tissue To the Metastatic Cascamentioning
confidence: 99%
“…Reshaping TME provides a niche for interaction between tumor cells and surrounding fibroblasts, endothelial cells, and immune cells [4,[6][7][8][9]. These cells interact with tumor cells through TME to induce a variety of biological events, such as appreciation, migration, angiogenesis, immunosuppression, and drug resistance for tumor development [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The chemokine and molecular profile of the cocultures was investigated further, and it was demonstrated that the cocultures showed increased levels of CXC12 and CXC7-chemokines consistently associated with increased tumor migration. In addition, increased levels of leptin and IL-8 seemed to be implicated in the more invasive phenotype of the cancer cells in the coculture, compared to the control [ 39 ]. Indeed, several studies in the past have associated leptin with tumor aggressiveness in other solid tumors.…”
Section: Tumor Immune Microenvironment In Adrenocortical Carcinomamentioning
confidence: 99%